Synthesis of Azabipyridine and Azaterpyridine Building Blocks for Multitopic Binding - De, Soumen; Pramanik, Susnata; Schmittel, Michael (Synthesis, 2012)
We describe the synthesis of four bromo-substituted azabipyridines and two bromo-substituted azaterpyridines through a series of palladium-catalyzed cross-coupling reactions. Both the azabipyridine and azaterpyridine heterocycles contain two orthogonal binding motifs, the value of which has been demonstrated recently in a nanomechanical switch for triggering organocatalysis. The bromo functionality allows heterocyclic ligands to be attached to larger frameworks.
Keywords: N-heterocycles; palladium catalysis; bipyridine; terpyridine; carbon–carbon coupling